An Inspection of hotel services’ Perceived Value Dimensions at Five Stars’ Hotels of Iraq - Alobaidi, Muthanna (Opción, 2019)
it was the thought which is say that the intention to recommend and return be- havior at the post-purchase stage influenced by the value of money that driven the arguments in this research. Perceived value is conceptualized as consisting of two dimensions: acquisition value and transaction value. The study utilized a scale developed by (Grewal et al., 1998) to hotel’s services. Although the scale was basically conducted to evaluate perceived value of product, so there were some concerns about its validity across the studies. In particular, although the dimension of acquisition value was found to be valid, transaction value showed poor validity. The conclusion suggests that a new conceptualization of transaction value and a better scale should be developed for the evaluation of hospitality services.